Changes in potential denitrification and respiration during the cold storage of soils - Simek, M (Folia microbiologica, 2000)
The denitrification potential in moderately fertilized soil sampled four times during 1995 decreased significantly after cold storage, at 4 +/- 2 degrees C for 1 week. Prolonged storage (up to 24 weeks) resulted in a further decrease of denitrification potential which dropped to 38-54% of the original values. Similarly, denitrification potential decreased substantially during the first week of storage in differently fertilized soils. After 24 weeks of storage, denitrification potential dropped to 29-55% of that in fresh soils. The effects of storage at 4 +/- 2 degrees C on denitrification potential and respiration (determined as carbon dioxide evolution) were in general the same in moderately fertilized soils from four different sites: in all soils, depression of both the denitrification potential and potential respiration was found after 8 weeks. However, the extent to which the parameters were decreased differed from case to case. Not only the duration and storage conditions but also unidentified soil parameters are important for the persistence of biological activity in stored soils.
Keywords: nízká teplota; dusičnany; Soil Microbiology; Cold Temperature; půdní mikrobiologie; Nitrates